PLIN2 Mediates Neuroinflammation and Oxidative/Nitrosative Stress via Downregulating Phosphatidylethanolamine in the Rostral Ventrolateral Medulla of Stressed Hypertensive Rats - Zhang S; Hu L; Han C; Huang R; Ooi K; Qian X; Ren X; Chu D; Zhang H; Du D; Xia C (Dove Medical Press, 2021)
Shutian Zhang,1,* Li Hu,2,* Chengzhi Han,1 Renhui Huang,1 Kokwin Ooi,1 Xinyi Qian,1 Xiaorong Ren,1 Dechang Chu,3 Haili Zhang,3 Dongshu Du,4 Chunmei Xia1 1Department of Physiology and Pathophysiology, School of Basic Medical Sciences, Fudan University, Shanghai, 200032, People's Republic of China; 2Department of Cardiology, Renji Hospital, School of Medicine, Shanghai Jiaotong University, Shanghai, 200240, People's Republic of China; 3College of Agriculture and Bioengineering, Heze University, Heze, 274000, People's Republic of China; 4School of Life Science, Shanghai University, Shanghai, 200444, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunmei XiaDepartment of Physiology and Pathophysiology, School of Basic Medical Sciences, Fudan University, Shanghai, 200032, People's Republic of ChinaTel +86 21 54237612-805Email cmxia@fudan.edu.cnDongshu DuSchool of Life Science, Shanghai University, Shanghai, 200444, People's Republic of ChinaEmail sdhzdds@163.comPurpose: Oxidative/nitrosative stress, neuroinflammation and their intimate interactions mediate sympathetic overactivation in hypertension. An immoderate inflammatory response is characterized not only by elevated proinflammatory cytokines (PICs) but by increases in mitochondrial dysfunction, reactive oxygen species (ROS), and nitric oxide (NO). Recent data pinpoint that both the phospholipid and lipid droplets (LDs) are potent modulators of microglia physiology.Methods: Stress rats underwent compound stressors for 15 days with PLIN2-siRNA or scrambled-siRNA (SC-siRNA) administrated into the rostral ventrolateral medulla (RVLM). Lipids were analyzed by mass spectroscopy-based quantitative lipidomics. The phenotypes and proliferation of microglia, LDs, in the RVLM of rats were detected; blood pressure (BP) and myocardial injury in rats were evaluated. The anti-oxidative/nitrosative stress effect of phosphatidylethanolamine (PE) was explored in cultured primary microglia.Results: Lipidomics analysis showed that 75 individual lipids in RVLM were significantly dysregulated by stress [PE was the most one], demonstrating that lipid composition changed with stress. In vitro, prorenin stress induced the accumulation of LDs, increased PICs, which could be blocked by siRNA-PLIN2 in microglia. PLIN2 knockdown upregulated the PE synthesis in microglia. Anti-oxidative/nitrosative stress effect of PE delivery was confirmed by the decrease of ROS and decrease in 3-NT and MDA in prorenin-treated microglia. PLIN2 knockdown in the RVLM blocked the number of iNOS+ and PCNA+ microglia, decreased BP, alleviated cardiac fibrosis and hypertrophy in stressed rats.Conclusion: PLIN2 mediates microglial polarization/proliferation via downregulating PE in the RVLM of stressed rats. Delivery of PE is a promising strategy for combating neuroinflammation and oxidative/nitrosative stress in stress-induced hypertension.Keywords: lipid droplets, PLIN2, phosphatidylethanolamine, lipidomics, microglial expansion, neuroinflammation, stress, RVLM, oxidative/nitrosative stress